DISKRIMINASI IMIGRAN KULIT PUTIH BERWARNA DALAM MASA KEBIJAKAN MULTIKULTURALISME PASCA PENGHAPUSAN WHITE AUSTRALIAN POLICY - Sandy Tieas Rahmana Poetrie (Lakon : Jurnal Kajian Sastra dan Budaya, 2013)
AbstractThis paper concern on the multiculturalism in Australia related to the immigration policy. Since the application of “White Australia Policy” which makes some restriction to people from other countries who are considered as different color and non-English speakers to come to Australia ended in 1907, the government attempts to eliminate the discrimination treatments to them all. This paper employs descriptive essay which was aimed to describe more aboutAustralian multiculturalism after the end of “White Australia Policy”. The technique of data collection was literary study from some sources like journals and some news from internet. The writer took three cases have ever happenedrelated to the multiculturalism in Australia to analyse the application of immigrants policy after “White Australia Policy” annulment. Those are Arabians beating in Sydney coast by Neo-Nazi, discrimination against Muslim minorityand Africans by police in Victoria, and also Muslim demonstration because of Muhammad humiliation. The study revealed that “White Australia Policy” still can not completely be eliminated. Those three cases, it shows that there arestill many discrimination treatments against coloured immigrants; on the other hand the government is still trying to implement a multiculturalism policy.